Sense and Sensibility - Austen, Jane, 1775-1817 (Salt Lake City, UT : Project Gutenberg, 1994)
"Sense and Sensibility" by Jane Austen is a novel published in 1811. When the Dashwood sisters are forced from their family estate into reduced circumstances, they face romantic trials that test their contrasting natures. Sensible Elinor guards her feelings while passionate Marianne wears her heart openly. Both encounter love, disappointment, and betrayal as suitors prove honorable or false. Through heartbreak and revelation, the sisters must navigate society's demands while discovering what truly matters in matters of the heart. (This is an automatically generated summary.)
There is an improved edition of this title, eBook #21839
Wikipedia page about this book: https://en.wikipedia.org/wiki/Sense_and_Sensibility
Release date is 1994-09-01
Keywords: England -- Social life and customs -- 19th century -- Fiction; Inheritance and succession -- Fiction; England -- Fiction; Young women -- Fiction; Love stories; Sisters -- Fiction; Domestic fiction; Mate selection -- Fiction; Social classes -- Fiction; Gentry -- England -- Fiction; Regency fiction